2014
DOI: 10.1186/1465-9921-15-46
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve and Lactobacillus rhamnosus treatment is as effective as budesonide at reducing inflammation in a murine model for chronic asthma

Abstract: BackgroundAsthma is estimated to affect as many as 300 million people worldwide and its incidence and prevalence are rapidly increasing throughout the world, especially in children and within developing countries. Recently, there has been a growing interest in the use of potentially beneficial bacteria for allergic diseases. This study is aimed at exploring the therapeutic effects of long-term treatment with two different beneficial bacterial strains (Bifidobacterium breve M-16 V and Lactobacillus rhamnosus Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 59 publications
1
79
0
1
Order By: Relevance
“…Lung cells were washed and resuspended in Roswell Park Memorial Institute 1640 culture medium (Lonza) supplemented with 10% heat-inactivated fetal calf serum and 0.1% penicillin-streptomycin solution (Sigma-Aldrich). Lung cells (4 3 10 5 cells/well) were cultured in medium with or without 50 mg/mL HDM (Greer Laboratories), and supernatant was harvested after 4 d of culture at 37°C in 5% CO 2 and stored at 220°C until further analysis (28).…”
Section: Methodsmentioning
confidence: 99%
“…Lung cells were washed and resuspended in Roswell Park Memorial Institute 1640 culture medium (Lonza) supplemented with 10% heat-inactivated fetal calf serum and 0.1% penicillin-streptomycin solution (Sigma-Aldrich). Lung cells (4 3 10 5 cells/well) were cultured in medium with or without 50 mg/mL HDM (Greer Laboratories), and supernatant was harvested after 4 d of culture at 37°C in 5% CO 2 and stored at 220°C until further analysis (28).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, several studies have reported that different strains of bifidobacteria can modulate T-cell responses in immune-driven diseases. In a murine model for chronic allergic asthma, Bifidobacterium breve M16-V was shown to increase Treg cell responses (defined as CD4 + FoxP3 + cells) and additionally increase the anti-inflammatory cytokine IL-10 in lung tissue [49]. This was also found to have similar effects as budesonide (i.e.…”
Section: T Cellsmentioning
confidence: 89%
“…In an obesity-associated inflammation model, B. pseudocatenulatum CECT 7765 reduced B-cell (CD19 + ) and pro-inflammatory macrophages (F4/80 + CD11c − CD206 + ), as well as increasing Treg responses, which correlated with reduced body weight gain and improved glucose tolerance [66]. Recently, B. breve pre-treatment was shown to significantly decrease the total inflammatory cell number, including decreasing the relative number of eosinophils and neutrophils in a murine airway inflammation model [49].…”
Section: Other Cells Typesmentioning
confidence: 99%
“…The Bifidobacteria are one of the major species of human colon microbiota and they are frequently used as probiotic agents [6]. Bifidobacterium species have immune modulatory, metabolic and anti-inflammatory effects which are not seen ın other gastro intestinal flora species [5,[7][8]. Bifidobacterium species have the highest level of intrinsic hydrogen peroxide resistance causing antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%